Pendampingan Pola Hidup Bersih dan Sehat pada Anak Sebagai Upaya Pencegahan Penularan Virus Corona - Sulastri, Ni Made; Herlina, Herlina; Sarilah, Sarilah (Jurnal Pengabdian UNDIKMA, 2021)
The aim of this community service is to provide assistance to a clean and healthy lifestyle for children as an effort to prevent the transmission of the corona virus. The method used in this service is in the form of assisting a clean and healthy lifestyle, providing knowledge of the dangers of the corona virus and its prevention, the question and answer method to find out the level of understanding of children after mentoring and demonstrations to practice one of the healthy lifestyles in the form of washing hands with soap. The result of this activity is an increase in children's knowledge of clean and healthy living behaviors in children. Increased knowledge about how to maintain a healthy lifestyle, one of which is by washing hands with the right technique, this can be seen in the ability of children to demonstrate handwashing activities with soap with the correct technique after being given assistance activities.